Somatic Mutations and the Risk of Undifferentiated Autoinflammatory Disease in MDS: An Under-Recognized but Prognostically Important Complication - Watad, Abdulla; Kacar, Mark; Bragazzi, Nicola Luigi; Zhou, Qiao; Jassam, Miriam; Taylor, Jan; Roman, Eve; Smith, Alexandra; Jones, Richard A.; Amital, Howard; Cargo, Catherine; McGonagle, Dennis; et al. (Frontiers in Immunology, 2021)
Objectives: We theorised that myelodysplastic syndrome (MDS) with somatic mutations and karyotype abnormalities are associated with autoinflammation, and that the presence of autoinflammatory disease affected prognosis in MDS. Methods: 134 MDS patients were assessed for the prevalence of autoinflammatory complications and its link with karyotypes and somatic mutation status. Autoinflammatory complications were described either as well-defined autoinflammatory diseases (AD) or undifferentiated “autoinflammatory disease” (UAD) (defined as CRP over 10.0 mg/l on 5 consecutive occasions, taken at separate times and not explained by infection). Several patient characteristics including demographic, clinical, laboratory, cytogenetics charts, and outcomes, were compared between different groups. Results: Sixty-two (46.3%) patients had an autoinflammatory complication manifesting as arthralgia (43.5% versus 23.6%, p=0.0146), arthritis (30.6% versus 15.3%, p=0.0340), skin rash (27.4% versus 12.5%, p=0.0301), pleuritis (14.5% versus 4.2%, p=0.0371) and unexplained fever (27.4% versus 0%, p<0.0001). AD were found in 7.4% of MDS patients (with polymyalgia rheumatic being the most frequently one). Classical autoimmune diseases were found only in 4 MDS patients (3.0%). Transcription factor pathway mutations (RUNX1, BCOR, WTI, TP53) (OR 2.20 [95%CI 1.02-4.75], p=0.0451) and abnormal karyotypes (OR 2.76 [95%CI 1.22-6.26], p=0.0153) were associated with autoinflammatory complications. Acute leukaemic transformation was more frequent in MDS patients with autoinflammatory features than those without (27.4% versus 9.7%, p=0.0080). Conclusions: Autoinflammatory complications are common in MDS. Somatic mutations of transcription factor pathways and abnormal karyotypes are associated with greater risk of autoinflammatory complications, which are themselves linked to malignant transformation and a worse prognosis.